Modern aspects of the use of foggy technologies in the educational process of higher educational institutions - Prokopenko, Аlena (My University, 2020)
The article considers the issues of improving the managerial and educational activities of higher education institutions through the use of cloudy and foggy innovative technologies. The author of the article on the basis of the analysis of scientific, pedagogical and specialized literature proves the relevance of research in this direction. This scientific legacy presents Google services that are appropriate to use in the educational process to increase its effectiveness and efficiency, as well as the feasibility of organizing and implementing an educational and scientific laboratory of innovative technologies.
Prokopenko A. Modern aspects of the use of foggy technologies in the educational process of higher educational institutions / A. Prokopenko // Освітні Обрії / Івано-Франків. обл. ін-т післядиплом. освіти пед. працівників. – 2020. – Вип. 1(50). – С. 98–101. Фахове видання
Keywords: innovative technologies, cloud technologies, fog computing, fog technologies, educational process; інноваційні технології, хмарні технології, туманні обчислення, туманні технології, освітній процес; инновационные технологии, облачные технологии, туманные вычисления, туманные технологии, образовательный процесс